One health system strengthening in India: Co-creating one health workforce to combat future pandemics - Sandul Yasobant; Deepak Saxena; Pankaj Bhardwaj; Zahiruddin Syed Quazi (Wolters Kluwer Medknow Publications, 2023)
One Health has been coming of age through the G7 and G20 leadership and explicitly referred to in increasing ministerial declarations. Those leaderships, however, have been slow in knitting the One Health approach into the larger systems approach. by understanding the complexity of resilience and health system resilience is one of the key features of pandemic preparedness. Among others, health system strengthening is another key factor that urgently requires much attention in the theme of pandemic preparedness. Here, how the health system strengthening requires more imperative attention in the One Health gambit is discussed in the Indian context.